The representation of the Lady of justice on the seventh art - Ramírez Salazar, Andrés Rodrigo (2019)
Law and Art have something in common: their humanistic character. On the other hand, justice, as an ideal, has been represented from the most varied cultural and artistic conceptions. The Western tradition, for example, offers us the image of a woman who uses a bandage on her face, armed in one hand with the scale of saucers and in the other with a sword, elements which allow us to play with that iconography. Then we endow it with a meaning: we assume that the bandage gives it honesty, that the scale weighs the arguments and that the sword forces to fulfill the woman’s decision. It intends to relate these typical attributes to the cinema, known as the seventh art, trying to understand the forms and ways to represent this popular image.